Biodecolourisation of reactive Red 120 as a sole carbon source by a bacterial consortium—toxicity assessment and statistical optimisation - Manogaran, Motharasan; Yasid, Nur Adeela; Othman, Ahmad Razi; Gunasekaran, Baskaran; Halmi, Mohd Izuan Effendi; Abd Shukor, Mohd Yunus (Multidisciplinary Digital Publishing Institute, 2021)
The application of microorganisms in azo dye remediation has gained significant attention, leading to various published studies reporting different methods for obtaining the best dye decolouriser. This paper investigates and compares the role of methods and media used in obtaining a bacterial consortium capable of decolourising azo dye as the sole carbon source, which is extremely rare to find. It was demonstrated that a prolonged acclimation under low substrate availability successfully isolated a novel consortium capable of utilising Reactive Red 120 dye as a sole carbon source in aerobic conditions. This consortium, known as JR3, consists of Pseudomonas aeruginosa strain MM01, Enterobacter sp. strain MM05 and Serratia marcescens strain MM06. Decolourised metabolites of consortium JR3 showed an improvement in mung bean’s seed germination and shoot and root length. One-factor-at-time optimisation characterisation showed maximal of 82.9% decolourisation at 0.7 g/L ammonium sulphate, pH 8, 35 °C, and RR120 concentrations of 200 ppm. Decolourisation modelling utilising response surface methodology (RSM) successfully improved decolourisation even more. RSM resulted in maximal decolourisation of 92.79% using 0.645 g/L ammonium sulphate, pH 8.29, 34.5 °C and 200 ppm RR120.